Balancing jurisdictional immunity of international organizations and the right to access to courts: the proportionality test - Aljahani, Abdelnaser (Human rights review, 2025)
The jurisdictional immunity of international organizations often conflicts with the right to access to courts. In the Waite and Kennedy case, the European Court of Human Rights (ECtHR) ruled that the recognition of jurisdictional immunity for an international organization depends on whether the organization has an internal dispute resolution mechanism that aggrieved individuals can access. The Court described this approach as the "test of proportionality." However, the ECtHR did not clarify the specific content of this proportionality test. In other words, the Court has not established clear standards for evaluating whether an organization’s internal dispute resolution mechanism meets the requirements of proportionality. This article seeks to establish a comprehensive framework for the proportionality test, particularly an exploration of its substantive standards. This will be achieved by analyzing the ECtHR’ judgment in the Waite and Kennedy case, as well as other related case law that has applied the proportionality test. The authors find that the Court in Waite and Kennedy case determined that aggrieved individuals must have "reasonable alternative means to protect effectively" their right to access to courts. Consequently, it can be argued that reasonableness and effectiveness are the key standards underlying the proportionality test. These standards should guide domestic courts when evaluating the adequacy of any internal dispute resolution mechanism provided by an international organization.